Underpinning The STEM Agenda Through Technological Textiles? An exploration of design technology teachers’ attitudes - Hughes, Chris; Bell, Dawne; Wooff, David (Design and Technology Education: An International Journal, 2011)
This paper discusses ongoing research into the role of design and technology education in emerging post industrial economies. Previous work (Hughes et al., 2010) focused on the changing characteristics of textiles technology in modern times and discussed how this could inform a design and technology curriculum related to the needs of a modern textile technology workforce. This current paper reports on the second stage of the grounded theory programme in which theoretically sampled data from the first phase provides the direction and purpose for the work presented here. Within this context, this research explores practising teachers’ perceptions of textile technology associated with the emergent STEM agenda. Data gathered supports the view that technological aspects of design and technology closely linked to the STEM agenda are needed to provide a firm foundation for the design aspects of the subject. Without a STEM focus, the subject may lose its hard won importance in the UK schools and colleges’ curriculum. This is especially the case in an economic climate in which curriculum design stakeholders may be forced to review the content of the national curriculum across all key stages as a whole.